Creativity manifestations in Lithuanian recreational sports: a case of the subculture of runners - Šatūnienė, Reda (Creativity Studies, 2024)
The paper analyzes manifestations of creativity in Lithuanian recreational runners’ leisure subculture in the latter 21st century’s decades. In this research, qualitative research methods: ethnography (observation, participant observation, visual data collection, research diaries), approach of socio-cultural anthropology have been employed. Empirical data, collected since mid-2015 up to the summer of 2023. Results demonstrate that contemporary recreational runners’ identities represent aesthetic visual and verbal (self)expression, creative strategies towards running-related practices, values of solitude, and community in parallel.